Palliative care physicians' perspectives of management for terminally ill cancer patients with death rattle: a nationwide survey. (18th May 2020) - Matsunuma, Ryo; Suzuki, Kozue; Matsuda, Yoshinobu; Mori, Masanori; Watanabe, Hiroaki; Yamaguchi, Takashi
Abstract: Death rattle occurs during the last days of life, and relatives of those afflicted frequently report that it is very distressful. However, there is no effective treatment for it. The purpose of this study was to investigate the perceptions of Japanese palliative care physicians in clinical practice in Japan. We conducted a nationwide survey of 268 physicians via an anonymous, self-report questionnaire. We assessed pharmacological and non-pharmacological management and anticholinergic agent choice. One hundred eighty-nine physicians (70.5%) returned the questionnaires. Fifty-five participants (29.1%) treating patients with Type-1 (real death rattle) and 36 participants (19%) treating patients with Type-2 (pseudo-death rattle) death rattle reported that they would frequently administer an anticholinergic agent. One-fourth would administer scopolamine butylbromide or scopolamine hydrobromide. In conclusion, more Japanese palliative care physicians thought that anticholinergic agents might be effective for treating Type-1 death rattle rather than Type-2. Further clinical trials of these agents are needed. Abstract : We investigated the perceptions of Japanese palliative care physicians for death rattle. One-third administer anticholinergic agents despite a lack of established evidence.